Data Security Transformation: The Significant Role of Blockchain Technology - Archa Erica; Silva Wulandari; Riya Widayanti (IAIC Bangun Bangsa, 2024)
Digital transformation has become a global trend that has reshaped the way businesses and governments operate worldwide. In Indonesia, both the government and the private sector are expediting digital transformation by embracing blockchain technology as a solution to enhance data security in daily operations. Several blockchain projects in Indonesia have been undertaken, such as the verification and validation of educational certificates, medical data storage, and payment systems. However, the implementation of blockchain technology in Indonesia is still facing various challenges, including unclear regulations, limited infrastructure, and a lack of understanding about blockchain technology. Therefore, support from all stakeholders is necessary to accelerate the adoption of blockchain technology in Indonesia. Further research and development must be conducted to maximize the potential of blockchain technology and hasten digital transformation in the country.